Factors influencing gender preference and awareness against sex determination in antenatal women in rural tertiary hospital in South India - G., Mahendra; R. P., Chaitra; Pukale, Ravindra S.; J. P., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Discrimination begins in the womb even before a baby is born. Sex ratio is an important social indicator that measures extent of prevailing equity between males and females in society and a balanced sex ratio is essential for a stable society. The main objective of this study is to find out the awareness of sex determination and to study the factors influencing gender preference among antenatal women. Methods: A cross-sectional, hospital-based study was done among antenatal women at Adichunchanagiri institute of medical sciences, B.G. Nagara, Mandya. Information regarding the type of family, number of family members, socioeconomic status, gender preference, factors influencing gender preference and obstetric details was collected after taking consent from the antenatal women attending the outpatient department in Adichunchanagiri institute of medical sciences as well as inpatient antenatal women. Details of about the awareness of sex determination and the perception of women regarding sex determination were also collected. Results: Total 114 pregnant women were included in this study. Among multigravidas 31.4% of them had male preference based on the sex of 1st baby being female, 44.7% (51) participants had son preference and 36% (41) had daughter preference and 19.3% (22) participants had no gender preference. Among study participants 95 (83.3%) of them were aware of punishment regarding sex determination and 19 (16.7%) of them were unaware of legal punishment. Conclusions: Awareness regarding sex determination facilities was found to be increased and pregnant women were also aware of the punishable act regarding sex determination. Factors influencing gender preference mainly included the gender of the first baby in multigravidas and the socioeconomic status.